Genotoxic and Cytotoxic Effects of Cone Beam Computed Tomography and Multidetector Computed Tomography on Exfoliated Buccal Epithelial Cells - Zahra Jahanshahiafshar; Hakimeh Ghorbani; Maryam Seyedmajidi; Mehrdad Nabahati; Kourosh Ebrahimnejad Gorji; Seyedali Seyedmajidi; Ehsan Moudi (Iranian Journal of Medical Sciences, 2023)
Background: Cone beam computed tomography (CBCT) and multidetector computed tomography (MDCT) are frequently used in dental and maxillofacial problems. This study aimed to assess the genotoxicity and cytotoxicity effects of CBCT and MDCT radiographies on exfoliated buccal epithelial cells during dental examinations. Methods: This prospective experimental study was conducted at Babol University of Medical Sciences (Babol, Iran) from March 2021 to April 2021. Buccal mucosa smears were collected bilaterally pre-exposure and 12 days after CBCT or MDCT examinations. To compare the frequency of micronuclei and other cytotoxic cellular changes such as pyknosis, karyolysis, and karyorrhexis, the paired sample t test and Wilcoxon test were used. In addition, independent sample t test, Mann-Whitney, and Chi square tests were used to investigate the differences between the imaging methods and between men and women. All statistical analyses were performed using the SPSS software, and P≤0.05 was considered statistically significant. Results: The current study included 60 adult patients (30 patients in each group), ranging in age from 21 to 50 years. The micronuclei and the other cytotoxic cellular changes increased significantly after CBCT and MDCT radiographic examinations on the 12th day compared to the pre-exposure results (P<0.001). MDCT had statistically higher cytotoxic and genotoxic effects than CBCT (9.4%, 23.1%, and 40% higher values in micronucleus frequency, the mean frequency of micronuclei, and other cytotoxic changes, respectively). There were no significant differences between men and women in the two examination methods (P=0.46 and P=0.49, respectively). Conclusion: Dental examinations with CBCT and MDCT can increase cytotoxicity and chromosomal damage in both men and women. Due to its lower radiation toxicities, CBCT can be recommended as an alternative to MDCT for dental examinations.